An Examination of the Remote Learning Management of the University of Rizal System: Optimizing Educational Outcomes - Francisco, Jonathan (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the remote learning management practices of the University of Rizal System (URS) and developed a proposed Remote Learning Management Program to optimize educational outcomes. Specifically, it explored the institutional strategies, policies, and initiatives implemented during the COVID-19 pandemic, assessed their translation into practice, evaluated their impact on student performance, enrollment, and retention, and identified innovations in teaching methodologies and institutional preparedness. The study employed a convergent parallel mixed-methods research design, integrating qualitative and quantitative approaches. Documentary analysis was conducted on institutional policies, strategic plans, and enrollment reports, while semi-structured interviews were administered to campus directors, deans, and faculty members from selected URS campuses offering Bachelor of Technology (BT) and Bachelor of Science in Information Technology (BSIT) programs. Quantitative institutional data and qualitative narratives were analyzed independently and synthesized to provide a comprehensive understanding of remote learning management. Findings revealed that URS successfully implemented flexible remote learning through customized learning management systems, strategic administrative support, and adaptive teaching methodologies. However, significant challenges persisted, including unstable internet connectivity, limited access to digital resources, varying levels of technological competence, reduced student engagement, and concerns regarding assessment integrity. Despite these constraints, faculty members demonstrated resilience by adopting innovative pedagogical strategies, while institutional leaders strengthened policies and support mechanisms to sustain learning continuity. Enrollment and retention trends indicated that strategic interventions contributed to maintaining educational participation during the pandemic. The study concluded that effective remote learning management requires an integrated approach combining technological infrastructure, faculty capability development, learner support services, responsive institutional policies, and continuous monitoring and evaluation. Based on the findings, a comprehensive Remote Learning Management Program was proposed to strengthen institutional readiness, enhance teaching effectiveness, improve student engagement, and ensure the sustainability of flexible learning modalities in higher education. The study contributes to the growing body of knowledge on educational management and provides a practical framework for higher education institutions seeking to improve remote learning delivery and optimize educational outcomes in the post-pandemic educational landscape.
Keywords: Remote Learning Management, Learning Management System, Educational Outcomes, Higher Education, Mixed-Methods, Institutional Support, University Of Rizal System, Flexible Learning, Educational Management, COVID-19.